Cikondang Blueprint: Mengungkap Pola Manajemen Sumber daya Dalam Arsitektur Tradisional Sunda - Bunga Putri Rezky; Devid Zafitra; Yusup Ade Putra; Rubi Wijaya; Gesta Faris Zabelva; Dhania Siti Hamidah; Davina Adinda Talita (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
Traditional architecture is a concrete manifestation of local wisdom that has developed through long-term interactions between humans, the environment, and cultural values. This study aims to examine resource management patterns embedded in the architecture of the Cikondang Traditional House as a representation of Sundanese culture. Traditional architecture not only reflects aesthetic values but also embodies a system of resource governance oriented toward sustainability (Rapoport, 2016). This research employs a descriptive qualitative approach using observation, in-depth interviews, and documentation techniques. The qualitative method is selected because it effectively explores the symbolic meanings and social practices inherent in traditional architecture (Creswell & Poth, 2018). The findings indicate that the Cikondang Traditional House implements modern management principles, including environment-based planning, social organization through mutual cooperation, and resource control governed by customary rules. These practices align with the concept of sustainable management, which emphasizes efficiency, participation, and ecological balance (Robbins & Coulter, 2018; United Nations, 2019).